Experiences and proposals to support work in favour of social justice from jesuit universities - Borja Vivanco Díaz (Miscelánea Comillas, 2016)
The action for social justice, which is a characteristic feature of the Society of Jesus, is of increasing importance to its universities. In this context, this paper proposes twelve ways to guide the promotion of social justice from these universities. The time has come for concrete measures and for putting theory into practice, and Jesuit universities need to take experiences or best practices as references in order to fight for social justice. In this article we offer specific guidelines and resources to help strengthen their work in this area, on the basis of qualitative and quantitative research conducted in different Jesuit universities, mainly in Spain.